Changes in the multi-joint kinematics and co-ordination after repetitive windsurfing pumping task - So, R.; Chan, K. M.; Appel, R.; Yuan, Y. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: This study investigated the change in kinematics after repetitive continuous maximal windsurfing pumping on a simulator by utilizing 3-D motion analysis. METHODS: Six competitive windsurfers exercised on a tailor-made simulator. The wind force was simulated by attaching the boom to the power head of a rowing ergometer. The exercise consisted of 3 sets of 3-minute maximum pumping. The motion of wrist, elbow, shoulder (on sagittal and frontal planes), waist, hip, knee and ankle joints were recorded by 2 video cameras. Kinematic analysis included the assessment of the change of the range of motion, movement speed (pulling phase and the whole pumping cycle), as well as the movement pattern of all tested joints. RESULTS: Modified motor strategy was documented by the significant drop of vertical excursion of the body centre of mass. Moreover, the ankle plantar flexors and dorsiflexors, mid-deltoid as well as wrist extensor and flexor, had significant change of movement according to the assessed parameters. Therefore, they may be the muscles that were more influenced than the other assessed muscles after continuous maximal pumping. The change of muscle co-ordination may be a compensation mechanism to maintain work output. CONCLUSIONS: Findings in this study may suggest the importance of implementing specific muscle training program for the competitive windsurfers to increase the pumping capacity.